Measurement of Revenue Receipt Buoyancy in Goa - Shanbhogue, Suresh; Ramesh, B. (Indian Journal of Finance, 2011)
Revenue receipt buoyancies in respect of different components of State's Own Tax and Non-Tax Revenues, Grants in Aid from Government of India and Share in Central Taxes have been measured using log-liner model. Data for 20 years of post-statehood period from 1987-88 to 2006-07 has been made use of. F-Statistic indicates high level of statistical significance in respect of all the sources of revenue receipt except Interest Receipt/Dividend and Grants in Aid from Government of India. The buoyancy estimates from log-linear model reveal that the buoyancy rate was more than 'unity' in case of State's Own Tax and Non-Tax Revenues except for State Excise, Land Revenue, Interest Receipt/Dividend and Non-Tax Revenue from General Services. The State may augment revenue collection from State Excise probably by revising the excise duty structure, which is presently far below in comparison with rest of the States. As the share capital investment made in the State Owned PSUs is not yielding any return, it is necessary that the government has to be more practical and professional in making share capital investment in PSUs and institutions. Government of Goa is not getting adequate central grants and share in central taxes in spite of its substantial contribution. Therefore, the State has to make a strong case before Government of India to suitably dovetail incentive mechanism in the devolution formula.